2015
DOI: 10.1089/brain.2014.0299
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Resting-State fMRI Functional Connectivity with Flow-BOLD Coupling and Regional Vasculature

Abstract: There has been tremendous interest in applying functional magnetic resonance imaging-based resting-state functional connectivity (rs-fcMRI) measurements to the study of brain function. However, a lack of understanding of the physiological mechanisms of rs-fcMRI limits their ability to interpret rs-fcMRI findings. In this work, the authors examine the regional associations between rs-fcMRI estimates and dynamic coupling between the blood oxygenation level-dependent (BOLD) and cerebral blood flow (CBF), as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 49 publications
8
48
0
Order By: Relevance
“…A similar finding was also reported in another study of humans (Tak et al, 2015). Our finding of decrease in both DMN and CBF of PCC is consistent with that reported in prior studies.…”
Section: Long-duration Effect Of Isoflurane On Dmn Of the Brainsupporting
confidence: 93%
“…A similar finding was also reported in another study of humans (Tak et al, 2015). Our finding of decrease in both DMN and CBF of PCC is consistent with that reported in prior studies.…”
Section: Long-duration Effect Of Isoflurane On Dmn Of the Brainsupporting
confidence: 93%
“…Underlying vascular heterogeneity might induce false-positive or -negative spatial correlations, however. In the resting state fMRI literature, the influence of cerebral blood flow (CBF) and vessel size on BOLD-FC is increasingly discussed (45), and recent studies suggest strong BOLD-CBF coupling (46,47). There is also evidence that these CBF fluctuations indicate reactivity to neuronal activity rather than to heterogeneous vascularity, however.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that these CBF fluctuations indicate reactivity to neuronal activity rather than to heterogeneous vascularity, however. Tak et al (46) also acquired data on large-vessel volume fraction and found that BOLD-FC was inversely related to macrovascular volume fraction. The stronger relationship with small-to medium-sized vessels (closer to neuronal activity) was particularly prominent for major FC hubs.…”
Section: Discussionmentioning
confidence: 99%
“…[ Figure 7] Tak and colleagues' subsequent work took the CBF-BOLD coupling analysis one step further to examine the relationship between the degree of coupling and the corresponding functional connectivity measurements (Tak et al, 2015). The analysis demonstrated that restingstate functional connectivity strength, in this case based on the BOLD signal, is stronger in regions of stronger CBF-BOLD coupling (Figure 8).…”
Section: Assessment Of Resting-state Neurovacular Physiologymentioning
confidence: 99%